Harnessing Solar Energy for Sustainable Urban Street Lighting - Tharo, Zuraidah; Sutejo, Eddy; SK, Gavana Mustaqim (CV. Science Tech Group, 2024)
Public street lighting plays an important role in enhancing safety and comfort in urban areas. However, the use of conventional energy for public street lighting significantly contributes to greenhouse gas emissions. This research aims to study the optimization of solar energy usage in public street lighting systems to reduce urban emissions. The methods used include energy efficiency analysis, case studies of solar energy-based public street lighting implementation, and environmental impact evaluation. The results of the study show that the application of solar energy technology in public street lighting can increase energy efficiency by up to 30% and reduce CO2 emissions by 25% compared to conventional systems. In the case study of public street lighting in the city of Binjai, the reduction in carbon emissions reached 99.96%. Additionally, this study also identifies key factors affecting the success of implementation, such as technical design, initial costs, and government policy support. Therefore, optimizing solar energy-based public street lighting not only has the potential to reduce negative environmental impacts but also supports sustainable urban development.